Digitalization and labor restructuring: Editorial - Martina Fuchs; Andrew Cumbers (ZFW - Advances in Economic Geography, 2023)
This editorial shows how the digital economy continuously reshapes work and employment. Based on a literature review, it illustrates that digitalization frequently implies job loss, de-skilling and measures to restrict co-determination and participation of labor. However, digitalization also offers opportunities for managers, employees and unions to create new work tasks and conditions for skilled work. After showing major trends of digitalization in the last decades, the editorial illustrates recent research fields in economic geography.
Keywords: 330; digitalization; labor; online retail; technology; trade union; work